Перспективи інтродукції водяного горіха плаваючого (Trapa natans L. s.l.) в Україні - Chorna, G.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2002)
Basing on our investigations and analysis of literature the modem distribution, history and prospects of introduction of Trapa natans L. s.l. as rare relict and decorative species in water reservoirs of the dendrological parks of Ukraine are described. Methods of widespread fruits have been analysed.